Pembelajaran Seni Teater Tradisional Daerah Setempat Menggunakan Metode Demonstrasi pada Siswa Kelas X di SMA Negeri 1 Rambang Dangku - Destiani , Versilia; Hasan, Hasan; Ilhaq, Muhsin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to find out the learning of traditional local theater using the demonstration method in class X students at SMA Negeri 1 Ramang Dangku. This research is a type of descriptive qualitative research method using one teacher, namely Mr. Ade Setiawan S. Pd as one of the class X cultural arts teachers and also 10 students consisting of 5 male students and also 5 female students. Based on the results of the study, shows that traditional theater learning using the demonstration method can run wellcompared to the lecture method. This can increase the enthusiasm of students to learn well.